Studi Kompetensi Technological Pedagogical Content Knowledge (TPACK) Mahasiswa Calon Konselor - Husnaningrum, Baiq Nyidiah R; Simon, Irene Maya; Setiyowati, Arbin Janu (Buletin Konseling Inovatif, 2025)
Technological Pedagogical Content Knowledge (TPACK) is a capability that needs to be possessed by school counselors and prospective school counselors to be able to provide guidance services, assess learning outcomes and processes as well as guidance services, conduct guidance and training effectively with technology that occurs in a variety of situations. This study aims to describe the TPACK competencies of prospective counselor students. The approach used in this research is descriptive qualitative research. Data were obtained from interviews, observations, and documentation studies. The data analysis stages are: the data reduction stage, data presentation, and the last is drawing of conclusions. The study results show that prospective counselor students can integrate technology with pedagogy to develop guidance service methods or content in the guidance service process.